Intelligent transportation systems from good practices to standards - Pagano, Paolo (CRC Press/Taylor & Francis, 2017)
Intelligent Transport Systems (ITS) are the way forward for sustainable growth of mobility at all levels (local, regional, national, transnational). The book reviews the current status of Research & Development. It includes connected (and autonomous) cars and buses, real-world large-scale field trials, data analysis and assessment of technological solutions.